Insulating rod body material with high corrosion resistance and preparation method thereof
By mixing and processing materials such as bisphenol epoxy resin, polybicyclopentadiene, modified glass fiber, etc., an insulating rod body material with high corrosion resistance is prepared, which solves the problems of poor aging resistance and safety risks of existing materials, and achieves high corrosion resistance, heat resistance, flame retardant and mechanical properties of the materials.
Patent Information
- Application Number
- CN202411810531.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing insulating rod body materials have poor aging resistance, which easily oxidizes, resulting in reduced mechanical properties, and low oxygen index, which poses safety risks, which limits its use.
Bisphenol epoxy resin, polybicyclopentadiene, modified glass fiber, curing agent, modifier and lubricant were mixed, and treated by a high-speed mixer and a twin-screw extruder to prepare insulating rod body materials with high corrosion resistance.
The corrosion resistance, heat resistance, flame retardant, oxidation resistance and mechanical properties of insulating rod body materials are significantly improved, ensuring the long-term stability and safety of the material.
Smart Images

Figure BDA0005180439170000031 
Figure BDA0005180439170000032 
Figure BDA0005180439170000041
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of insulating rods, and in particular, relates to an insulating rod body material with high corrosion resistance and a preparation method thereof. Background Art
[0002] The insulating rod, also known as the switch rod or the link rod, consists of two parts: the working head and the insulating rod body. It is an insulating tool mainly used for short-term operation of live equipment, such as connecting or disconnecting high-voltage disconnectors, drop fuses, installing and removing portable grounding wires, as well as for measurement and testing. The insulating rod is one of the most commonly used safety tools for grassroots rural power workers and is widely used in power work.
[0003] The performance of the insulating rod mainly depends on the rod body material of the insulating rod. At present, the rod body material of the insulating rod is widely used solid composite insulating material. Among these materials, epoxy resin is widely used as the rod body material of the insulating rod due to its excellent corrosion resistance. However, the aging resistance of epoxy resin is poor. If it is used for a long time, the oxygen in the air will oxidize the epoxy resin and reduce its mechanical properties. Moreover, the oxygen index of epoxy resin is low. When engaged in electrical work, the safety risk is high, which limits its use. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of insulating rod technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an insulating rod body material with high corrosion resistance and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing an insulating rod body material with high corrosion resistance comprises the following steps:
[0007] Bisphenol epoxy resin, polydicyclopentadiene, modified glass fiber, curing agent, modifier and lubricant are mixed and added into a high-speed mixer and mixed for 30 minutes to fully mix the components. The mixture is then poured into a twin-screw extruder for melt blending and extrusion. The material is cooled to room temperature after discharge to obtain an insulating rod body material with high corrosion resistance.
[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of bisphenol epoxy resin, 20-30 parts of polydicyclopentadiene, 6-18 parts of modified glass fiber, 1-3 parts of curing agent, 5-15 parts of modifier, and 2-4 parts of lubricant.
[0009] Furthermore, the curing agent is one of 2-methylimidazole, 2-ethyl-4-methylimidazole and 2-ethylimidazole.
[0010] Furthermore, the lubricant is one of paraffin and epoxidized soybean oil.
[0011] With bisphenol epoxy resin as the matrix, the rod material is endowed with excellent corrosion resistance; the added polydicyclopentadiene not only has good insulation properties, but also can improve the heat resistance and mechanical properties of the rod material.
[0012] Furthermore, the modified glass fiber is prepared by the following steps:
[0013] A1. Add glass fiber into a beaker, then add hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4-6 hours, filter, and dry to obtain hydroxylated glass fiber;
[0014] A2. Mix the hydroxylated glass fiber obtained in step A1 with acetone and silane coupling agent KH-550, heat to 85° C., react for 4-6 hours, filter, and vacuum dry to obtain modified glass fiber.
[0015] Furthermore, the raw materials are calculated in parts by weight as follows: 1-5 parts of glass fiber, 20-40 parts of hydrogen peroxide, 40-60 parts of acetone, and 5-15 parts of silane coupling agent KH-550.
[0016] Glass fiber is a high-strength filling material. The surface of the glass fiber is modified by using the silane coupling agent KH-550 to enhance its surface hydrophobicity, improve the compatibility of the glass fiber with the epoxy resin matrix, make the modified glass fiber evenly dispersed in the matrix, reduce the occurrence of agglomeration, and greatly enhance the mechanical strength of the insulating rod material.
[0017] Furthermore, the modifier is prepared by the following steps:
[0018] S1. Add methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrafluorobutanediol, lithium diisopropylamide (catalyst, LAD) and N,N-dimethylformamide (DMF) into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove all air, heat to 80°C, keep warm for 6 hours, and after the reaction is completed, remove the solvent by vacuum distillation, wash with anhydrous ethanol 2-3 times to obtain intermediate 1; the ratio of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, tetrafluorobutanediol, lithium diisopropylamide and N,N-dimethylformamide is 29.2g:17.5g:0.4g:150mL;
[0019] Under the catalysis of lithium diisopropylamide, methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tetrafluorobutanediol undergo an ester exchange reaction. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of tetrafluorobutanediol, only one hydroxyl group on tetrafluorobutanediol participates in the reaction to obtain intermediate 1. The specific reaction process is as follows:
[0020]
[0021] S2, in a three-necked flask equipped with a stirring reflux device, the intermediate 1, phenylphosphonyl dichloride and toluene were mixed, and then diethylamine (acid binding agent) was added, and the temperature was controlled to react for 6 hours at 65°C. After the reaction was completed, diethylamine hydrochloride was filtered, and part of the solvent was removed by vacuum distillation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, phenylphosphonyl dichloride, toluene, and diethylamine was 42.2g:20.2g:150mL:15mL;
[0022] Intermediate 1 undergoes a nucleophilic substitution reaction with phenylphosphonyl dichloride. By controlling the molar ratio of the two to be close to 1:1 and the phenylphosphonyl dichloride to be slightly excessive, only one -Cl on the phenylphosphonyl dichloride participates in the reaction. Diethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 2. The specific reaction process is shown below:
[0023]
[0024] S3. In a three-necked flask equipped with a stirring device, the intermediate 2, 1,3-propylenediamine, diethylamine and toluene were mixed and stirred uniformly at room temperature, nitrogen was introduced into the device as a protective gas, the temperature was gradually raised to 60°C, and the reaction was kept warm for 5 hours. After the reaction was completed, diethylamine hydrochloride was filtered out, and part of the solvent was removed by reduced pressure distillation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, 1,3-propylenediamine, diethylamine and toluene was 57.9 g:8.4 g:15 mL:150 mL;
[0025] Intermediate 2 and 3-propylenediamine undergo nucleophilic substitution, and diethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 3. The specific reaction process is as follows:
[0026]
[0027] S4. In a three-necked flask equipped with a stirring device, p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide (DMSO) were mixed, tributyltin (catalyst) was added and mixed and stirred evenly, the temperature was gradually increased to 70°C, and the reaction was kept warm for 6 hours. Stirring was continued during the reaction. After the reaction was completed, the solvent was removed by vacuum distillation, and the mixture was dried in vacuo to obtain a modifier; the ratio of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin was 17.4g:61.8g:200mL:0.2g;
[0028] The isocyanate group in p-phenylene diisocyanate reacts with the amino group on the intermediate 3 to generate a urea group. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of p-phenylene diisocyanate, only one isocyanate group on p-phenylene diisocyanate participates in the reaction to obtain a modifier. The specific reaction process is as follows:
[0029]
[0030] The modifier molecule prepared by the present invention contains CF bond, PN flame retardant component, hindered phenol and isocyanate group, wherein the CF bond has small polarity and strong bond energy, the higher the chemical bond energy, the better the stability, which not only improves the heat resistance of epoxy resin matrix, but also the CF bond can well coat CC main chain and improve the corrosion resistance of matrix; the introduced PN flame retardant component has the synergistic flame retardant effect of phosphorus and nitrogen flame retardants, and can greatly improve the flame retardant performance of matrix; the introduced hindered phenol group belongs to phenolic antioxidant, the structure of such antioxidant contains -OH functional group, and -OH functional group is easy to react in the reaction. It is easy to provide H atoms, and this process is achieved through proton donation, which destroys the auto-oxidation of free radicals in the chain reaction, achieves an antioxidant effect, and can enhance the antioxidant properties of the matrix; finally, the isocyanate group in the modifier molecule can react with the epoxy group in the epoxy resin matrix to generate a five-membered ring oxazolidinone structure, which can further improve the heat resistance of the epoxy resin matrix and enhance the mechanical properties of the matrix to a certain extent; not only that, the modifier and the epoxy resin matrix are connected by chemical bonds, which improves the migration and exudation resistance of the modifier small molecule and improves the stability of the modifier.
[0031] Beneficial effects of the present invention:
[0032] 1. The rod material prepared by the present invention uses bisphenol epoxy resin as a matrix, which gives the rod material excellent corrosion resistance;
[0033] 2. By adding modified glass fiber, compared with ordinary glass fiber, it has better compatibility with the epoxy resin matrix, the agglomeration phenomenon is significantly reduced, and the mechanical properties of the rod material are greatly enhanced;
[0034] 3. The various groups in the prepared modifier work synergistically, significantly improving the flame retardancy, heat resistance and oxidation resistance of the rod material, further enhancing the corrosion resistance and mechanical properties of the rod material, and the performance is long-term and stable;
[0035] Therefore, the rod body material prepared by the present invention has stable and efficient flame retardant, heat-resistant, antioxidant and corrosion-resistant properties, and excellent mechanical properties, and has important application value in the field of insulating rod technology. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1
[0038] Preparation of modifier:
[0039] S1. Add 29.2 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 17.5 g of tetrafluorobutanediol, 0.4 g of lithium diisopropylamide and 150 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove air, heat to 80° C., keep warm for 6 hours, and after the reaction is completed, remove the solvent by distillation under reduced pressure, and wash with anhydrous ethanol 2-3 times to obtain intermediate 1;
[0040] S2, in a three-necked flask equipped with a stirring reflux device, 42.2g of intermediate 1, 20.2g of phenylphosphonyl dichloride and 150mL of toluene were mixed, and then 15mL of diethylamine was added, and the temperature was controlled to react for 6h at 65°C. After the reaction was completed, diethylamine hydrochloride was filtered, and part of the solvent was removed by distillation under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;
[0041] S3, at room temperature, in a three-necked flask equipped with a stirring device, 57.9 g of intermediate 2, 8.4 g of 1,3-propylenediamine, 15 mL of diethylamine and 150 mL of toluene were mixed and stirred evenly, nitrogen was introduced into the device as a protective gas, and the temperature was gradually raised to 60° C., and the reaction was kept warm for 5 hours. After the reaction was completed, diethylamine hydrochloride was filtered out, and part of the solvent was removed by reduced pressure distillation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0042] S4. In a three-necked flask equipped with a stirring device, 17.4 g of p-phenylene diisocyanate, 61.8 g of intermediate 3 and 200 mL of dimethyl sulfoxide were mixed, 0.2 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain a modifier.
[0043] Embodiment 2
[0044] Preparation of modifier:
[0045] S1. Add 58.4 g of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 35 g of tetrafluorobutanediol, 0.8 g of lithium diisopropylamide and 300 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, pass nitrogen to remove all air, heat to 80° C., keep warm for 6 hours, and after the reaction is completed, remove the solvent by distillation under reduced pressure, wash twice with anhydrous ethanol to obtain intermediate 1;
[0046] S2, in a three-necked flask equipped with a stirring reflux device, 84.4g of intermediate 1, 40.4g of phenylphosphonyl dichloride and 300mL of toluene were mixed, and then 30mL of diethylamine was added, and the temperature was controlled to react for 6h at 65°C. After the reaction was completed, diethylamine hydrochloride was filtered, and part of the solvent was removed by distillation under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;
[0047] S3, at room temperature, in a three-necked flask equipped with a stirring device, 115.8 g of intermediate 2, 16.8 g of 1,3-propylenediamine, 30 mL of diethylamine and 300 mL of toluene were mixed and stirred evenly, nitrogen was introduced into the device as a protective gas, the temperature was gradually raised to 60 ° C, and the reaction was kept warm for 5 hours. After the reaction was completed, diethylamine hydrochloride was filtered out, and part of the solvent was removed by reduced pressure distillation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:3), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0048] S4. In a three-necked flask equipped with a stirring device, 34.8 g of p-phenylene diisocyanate, 123.6 g of intermediate 3 and 400 mL of dimethyl sulfoxide were mixed, 0.4 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain a modifier.
[0049] Embodiment 3
[0050] Preparation of modified glass fiber:
[0051] A1. Add 1g of glass fiber to a beaker, then add 20g of hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 4h, filter, and dry to obtain hydroxylated glass fiber;
[0052] A2. Mix the hydroxylated glass fiber obtained in step A1 with 40 g of acetone and 5 g of silane coupling agent KH-550, heat to 85° C., react for 4 hours, filter, and vacuum dry to obtain modified glass fiber.
[0053] Embodiment 4
[0054] Preparation of modified glass fiber:
[0055] A1. Add 5 g of glass fiber into a beaker, then add 40 g of hydrogen peroxide dropwise, stir and mix evenly, heat to 110°C, reflux for 6 hours, filter, and dry to obtain hydroxylated glass fiber;
[0056] A2. Mix the hydroxylated glass fiber obtained in step A1 with 60 g of acetone and 15 g of silane coupling agent KH-550, heat to 85° C., react for 6 h, filter, and vacuum dry to obtain modified glass fiber.
[0057] Embodiment 5
[0058] 80g of bisphenol epoxy resin, 20g of polydicyclopentadiene, 6g of modified glass fiber prepared in Example 3, 1g of 2-methylimidazole, 5g of the modifier prepared in Example 1 and 2g of paraffin were mixed, added to a high-speed mixer, mixed for 30 minutes to fully mix the components, poured into a twin-screw extruder for melt blending and extrusion, and cooled to room temperature after discharge to obtain an insulating rod body material with high corrosion resistance.
[0059] Embodiment 6
[0060] 90g of bisphenol epoxy resin, 25g of polydicyclopentadiene, 12g of modified glass fiber prepared in Example 4, 2g of 2-ethyl-4-methylimidazole, 10g of the modifier prepared in Example 2 and 3g of paraffin were mixed, added to a high-speed mixer, mixed for 30 minutes to fully mix the components, poured into a twin-screw extruder for melt blending and extrusion, and cooled to room temperature after discharge to obtain an insulating rod body material with high corrosion resistance.
[0061] Embodiment 7
[0062] 100 g of bisphenol epoxy resin, 30 g of polydicyclopentadiene, 18 g of modified glass fiber prepared in Example 4, 3 g of 2-ethylimidazole, 15 g of the modifier prepared in Example 2 and 4 g of epoxy soybean oil were mixed, added to a high-speed mixer, and mixed for 30 minutes to fully mix the components. The mixture was then poured into a twin-screw extruder for melt blending and extrusion. The material was cooled to room temperature after discharge to obtain an insulating rod body material with high corrosion resistance.
[0063] Comparative Example 1
[0064] The modifier in Example 7 was replaced by a commercially available flame retardant of equal mass, and the remaining steps were the same as those in Example 7 to obtain a rod material.
[0065] Comparative Example 2
[0066] Use commercially available corrosion-resistant epoxy resin materials.
[0067] Embodiments 5, 6 and 7, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:
[0068] The national standard GB 13398-2003 "Hollow insulating tubes, foam-filled insulating tubes and solid insulating rods for live working" is used to measure the tensile strength and normal resistivity;
[0069] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 30 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the tensile strength of the sample after aging (GB13398-2003), and calculate the tensile strength retention rate; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;
[0070] Thermal aging test: Place the sample in an environment of 160°C, let it stand for 12 hours, then test the tensile strength of the sample (GB13398-2003), and calculate the tensile strength retention rate;
[0071] Determine the tensile strength of the sample after alkali treatment and acid treatment (GB 13398-2003), and calculate the tensile strength retention rate;
[0072] Alkali treatment: sodium hydroxide solution with a pH value of 13 in a 55°C water bath for 4 hours;
[0073] Acid treatment: hydrochloric acid solution with a pH value of 2 in a water bath at 55°C for 4 hours;
[0074] The flame retardant properties of the samples were measured before and after 180 days according to the UL-94 standard;
[0075] The measured results are shown in the following table:
[0076]
[0077] It can be seen from the above table that the rod material prepared in the embodiment of the present invention has higher flame retardancy, heat resistance, oxidation resistance, corrosion resistance and mechanical properties than the control example, and the performance is long-lasting and stable, which has important application value in the field of insulating rod technology.
[0078] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0079] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing an insulating rod body material with high corrosion resistance, comprising the following steps: Bisphenol epoxy resin, polydicyclopentadiene, modified glass fiber, curing agent, modifier and lubricant are mixed, added into a high-speed mixer, mixed, poured into a twin-screw extruder for melt blending and extrusion, and cooled to room temperature after discharge to obtain an insulating rod body material with high corrosion resistance.
2. The method for preparing an insulating rod body material with high corrosion resistance according to claim 1, characterized in that: The modifying agent is prepared by the following steps: S1. Methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrafluorobutanediol, lithium diisopropylamide and N,N-dimethylformamide were stirred and mixed evenly, and then nitrogen was passed to remove all air. The temperature was raised to 80° C. and the reaction was kept at this temperature for 6 hours. After the reaction was completed, the reaction was distilled under reduced pressure and washed to obtain intermediate 1. S2, mixing intermediate 1, phenylphosphonyl dichloride and toluene, adding diethylamine, reacting at 65°C for 6 hours, filtering, distilling under reduced pressure, purifying by column chromatography, and rotary evaporating to obtain intermediate 2; S3, at room temperature, the intermediate 2, 1,3-propylenediamine, diethylamine and toluene were mixed and stirred evenly, nitrogen was introduced into the device, the temperature was gradually raised to 60°C, and the temperature was kept for reaction for 5 hours. After the reaction was completed, the intermediate 3 was obtained by filtration, vacuum distillation, column chromatography purification, and rotary evaporation. S4. Mix p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide, add tributyltin and mix well, gradually increase the temperature to 70°C, keep the temperature for 6 hours, stir continuously during the reaction, and after the reaction is completed, perform vacuum distillation and vacuum drying to obtain a modifier.
3. The method for preparing an insulating rod body material with high corrosion resistance according to claim 2, characterized in that: In step S1, the ratio of the amount of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrafluorobutanediol, lithium diisopropylamide, and N,N-dimethylformamide is 29.2 g:17.5 g:0.4 g:150 mL.
4. The method for preparing an insulating rod body material with high corrosion resistance according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, phenylphosphonic acid dichloride, toluene and diethylamine is 42.2 g: 20.2 g: 150 mL: 15 mL.
5. The method for preparing an insulating rod body material with high corrosion resistance according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, 1,3-propylenediamine, diethylamine and toluene is 57.9 g:8.4 g:15 mL:150 mL.
6. The method for preparing an insulating rod body material with high corrosion resistance according to claim 2, characterized in that: In step S4, the ratio of the amount of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin is 17.4 g:61.8 g:200 mL:0.2 g.
7. The method for preparing an insulating rod body material with high corrosion resistance according to claim 1, characterized in that: The modified glass fiber is prepared by the following steps: A1. Add glass fiber and hydrogen peroxide into a beaker, stir and mix evenly, heat to 110°C, reflux for 4-6 hours, filter, and dry to obtain hydroxylated glass fiber; A2. Mix the hydroxylated glass fiber obtained in step A1 with acetone and silane coupling agent KH-550, heat to 85° C., react for 4-6 hours, filter, and vacuum dry to obtain modified glass fiber.
8. The method for preparing an insulating rod body material with high corrosion resistance according to claim 7, characterized in that: The raw materials are calculated in parts by weight as follows: 1-5 parts of glass fiber, 20-40 parts of hydrogen peroxide, 40-60 parts of acetone, and 5-15 parts of silane coupling agent KH-550.
9. The method for preparing an insulating rod body material with high corrosion resistance according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of bisphenol epoxy resin, 20-30 parts of polydicyclopentadiene, 6-18 parts of modified glass fiber, 1-3 parts of curing agent, 5-15 parts of modifier, and 2-4 parts of lubricant.
10. An insulating rod body material with high corrosion resistance, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Fluorine atom-containing phenol compound
CN104837805A
Composition for forming gate insulating film, organic thin film transistor, electronic paper, and display device
CN105264648A
Epoxy resin-based high-bending-modulus polydicyclopentadiene and preparation method thereof
CN114479351A
Preparation method of high-thermal-conductivity epoxy composite insulating material based on diamond filling
CN117700937A
Composition for forming gate insulating film, organic thin film transistor, electronic paper, and display device
EP3382745A1